2009
DOI: 10.1109/tns.2009.2013239
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Assurance Test Guideline for Qualifying Devices for Use in Proton Environments

Abstract: Proton-induced single-event effects hardness assurance guidelines are developed to address issues raised by recent test results in advanced IC technologies for use in space environments. Specifically, guidelines are developed that address the effects of proton energy and angle of incidence on single-event latchup and the effects of total dose on single-event upset. The guidelines address both single-event upset (SEU), single-event latchup (SEL), and combined SEU and total ionizing dose (TID) effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It has been shown that heavy-Z materials present in devices increase the SEL cross section during proton testing due to the high-LET recoils created by nuclear reactions [1]. To understand if electrons are similarly capable of producing fragments with LET values high enough to induce this effect, a tungsten nuclear fragment simulation was performed.…”
Section: Fluka Tungsten Fragment Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that heavy-Z materials present in devices increase the SEL cross section during proton testing due to the high-LET recoils created by nuclear reactions [1]. To understand if electrons are similarly capable of producing fragments with LET values high enough to induce this effect, a tungsten nuclear fragment simulation was performed.…”
Section: Fluka Tungsten Fragment Simulationmentioning
confidence: 99%
“…One of the more dangerous among these is the single-event latchup (SEL), because the only way to remove the potentially destructive effect is to power cycle the device. A large body of work exists describing the approaches behind and radiation hardness assurance (RHA) qualification for SEL induced by protons [1]- [3] and neutrons [4]. Likewise, work is available showing electrons are capable of producing soft errors [5]- [7], however, no experimental evidence of hard failures is so far available.…”
Section: Introductionmentioning
confidence: 99%